Environmental Estimates and Effectiveness of BIPV (Building Integrated Photovoltaic)-Based Sustainable Homes in Khartoum Suburban - Abdallah Elhassan, Zeinab (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This study assesses energy conservation for urban building designers. The appropriate design for daily climate factors. These two issues are essential to urban energy as the major principles, especially in developing countries with hot, dry climates. Generally, they are considered a combination of an improved design that meets the user’s environmental need to apply the sustainability of urban areas that manages environmental concerns to produce the most energy-efficient urban or residential design by using BIPV. The study’s primary goals are to evaluate environmental indicators in domestic settlements using BIPV in Khartoum and to develop urban planning strategies for implementing residential building design (BIPV). The method began with a survey at(Alazhari City ) a Suburban of Khartoum. Citizen users of this technology, the study concluded that environmental characteristics must be included in the design to avoid errors and that the public accepts the BIPV. Architects can also design a low-cost, easy-to-maintain plan. With system funding, authorities can import it. Individually. The urban strategy level approaches are expected to have environmental and sustainability planning. The building serves the tenants’ activities. A house utilizing (BIPV) systems in the urban area of Khartoum was created with high functionality, durability, and beauty, including sustainability and the whole requirement of architectural design with its adequate environmental effects.